Hieron: the ancient sanctuary at the mouth of the Black Sea - Moreno, A (American School of Classical Studies at Athens, 2008)
This paper aims to present all of the currently available literary and archaeological evidence on the sanctuary of Hieron at the mouth of the Black Sea, including the previously unpublished record of its only known excavation. The evidence is analyzed in separate topographical, historical and archaeological sections, with a map and photographs, thus providing the most complete description of Hieron to date, showing how the entrance to the Black Sea was perceived in spatial and religious terms, and encouraging a future archaeological exploration that could increase our understanding of ancient trade and settlement in the Black Sea.